Molecular cloning of cDNAs from human kidney coding for two alternatively spliced products of the cardiac Ca2+-ATPase gene. - Jonathan Lytton; David H. MacLennan (1988)
Abstract Ca2+-ATPase molecules present in the microsomal fraction from non-muscle cells were examined immunologically. Rabbit whole brain, cerebellum, liver, kidney, and COS-1 cell microsomes all displayed a polypeptide of about 110 kDa which was immunoreactive with a polyclonal antiserum against the cardiac muscle sarcoplasmic reticulum Ca2+-ATPase molecule, but was not immunoreactive with a monoclonal antibody specific for the fast-twitch muscle Ca2+-ATPase. cDNAs encoding the full length of two Ca2+-ATPase molecules were isolated from a human kidney library using a mixture of nucleotide probes derived from both rabbit fast-twitch and cardiac muscle Ca2+-ATPase cDNAs. The human kidney cDNAs, HK1 and HK2, are the products of alternative splicing. HK2 codes for a protein identical to rabbit cardiac muscle Ca2+-ATPase, with the exception of 6 scattered amino acid replacements, whereas HK1 codes for a protein identical to that encoded by HK2, but with the carboxyl-terminal 4 amino acids replaced by an extended sequence of 49 amino acids. cDNAs of the HK1 type are by far the most abundant in the library. The partial structure of a 40-kilobase genomic DNA encoding all but the 5' end of the human cardiac Ca2+-ATPase is described. The exons which give rise to the alternatively spliced products were located by Southern blotting and sequencing, and the alternative splicing patterns were determined.